Enriched extracts of anti-diabetic compounds from neglected weed M. Pudica using supercritical and subcritical carbon dioxide extractions and the corresponding in vitro study for diabetes mellitus - Tunna, Tasnuva Sarwar; Sarker, Md. Zaidul Islam; Ahmed, Qamar Uddin; Md. Jaffri, Juliana; Ferdoush, Sahena (2016)
Medicinal plants and various extracts are traditionally used to treat ailments, disease and infections. Traditionally, organic solvents, water and oil were and are still used for the extraction of herbal medicine and often boiling (percolation) and vigorous techniques to separate the bioactive compounds were employed. Along with the advent of green technology and extraction methods, organic solvent-free extract preparation is on the rise. The current study aimed to undergo enrichment of chosen pre-isolated anti-diabetic compounds from M. pudica. The current study was employed using supercritical CO2 extraction (SFE) and subcritical CO2 Soxhlet by studying parameters of temperature, pressure, modifier or co-solvent and flow rate of CO2. It was found that the SFE and CO2-Soxhlet can be utilized to collect extract enriched with anti-diabetic compounds, which are stigmasterol, quercetin and avicularin from M. pudica in a clean and healthier method for future anti-diabetic implications.